Geotechnical Characterization of Marl OF Fa’tha Rocks for Zurbatiyah Region, East Iraq - Ali M. Hadi; Jaffar H. Al-Zubaydi (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
An investigation into the geotechnical properties of marl rocks from the Zurbatiyah zone was conducted. Characterization of physical attributes revealed dry densities spanning 2.120 g/cm³ to 2.370 g/cm³, specific gravity from 2.50 to 2.660, porosity from 8.7% to 19.23%, and water absorption from 3.69% to 8.99%. Chemical compositions, focusing on major oxides (MgO, CaO, Fe2O3, SiO2, Al2O3, SO2, and LOI), confirmed that their proportions fall within the acceptable ranges for cement industry raw materials, supported by Chaterjee (2018) and Iraqi standard specification (IQS-5:1984). The engineering properties assessment indicated a moderate strength profile, with uniaxial compressive strength values ranging from 21.80 MPa to 45.50 MPa